SURVEI PEMETAAN MINAT EKSTRAKURIKULER DAN KONDISI FASILITAS OLAHRAGA DI SMP NEGERI 21 BATANG HARI - Poniah Nenengsih; Atri Widowati; Fitri Diana (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The educational system needs to provide comprehensive development opportunities for students beyond classroom learning, with extracurricular activities serving as an important platform for personal growth and skill development. This research aimed to determine students' interest in extracurricular activities, quantify student participation rates, and assess the adequacy of sports facilities and infrastructure at SMP Negeri 21 Batang Hari. This study employed a mixed methods approach, combining quantitative and qualitative methodologies. The research sample consisted of students from grades VII and VIII at SMP Negeri 21 Batang Hari, with data collected through surveys, observations, and facility assessments. The findings revealed that SMP Negeri 21 Batang Hari offers five extracurricular sports programs, with futsal emerging as the most popular choice among both seventh and eighth-grade students. Overall student interest in extracurricular activities was categorized as moderate based on participation metrics and survey responses. The assessment of sports facilities indicated significant inadequacies in available infrastructure to support the full range of extracurricular programming. Student interest in sports extracurricular activities exists at a moderate level, with concentrated interest in futsal, suggesting opportunities for targeted program development while addressing the limitations in sports facilities. The study was limited to a single school environment; future research should explore the relationship between facility adequacy and participation rates across multiple schools, and investigate potential interventions to improve infrastructure support for extracurricular activities.